Learn MongoDB by building ten projects - Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"MongoDB is a cross-platform document-based database management system that is based on NoSQL. What makes it stand out from the rest of the database systems is that it foregoes the traditional table-based relational database structure and instead opts for JSON-like documents with dynamic schemas, known as BSON. This results in MongoDB being able to run on a small RAM and is comparatively faster than a lot of DBMS out there.With this comprehensive and well structured project based course, you will learn the ins and outs of how to work with MongoDB. You(19)ll understand and incorporate Mongo DB in your own business and learn its features and benefits with hands on learning experience. You will create fully functional database systems in MongoDB using this extensive online tutorial and become a master in all things MongoDB. Additionally, you will also get to learn a lot of other technologies that can be used in accordance with MongoDB, and the concepts will be broken down for you."--Resource description page.
Title and publication information from resource description page (Safari, viewed January 10, 2017).
Keywords: MongoDB; Database management -- Computer programs; Electronic books